The Effect of Digital Transformation on the Operational Efficiency of SMEs in Vietnam - Nguyen Thi Phuong , Dung; Nguyen Hieu , Khuong; Nguyen Phu , Son; Nguyen Trong , Tinh; Vo Van, Dang; Nguyen Truc , Huynh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The study aims to examine the effect of digital transformation on the operational efficiency of SMEs in Vietnam. Data were collected from SMEs listed on the stock exchange in Vietnam during the period of 2018–2022. The Generalized Least Squares (GLS) estimation method was employed to test the relationships among factors in the theoretical model. The research findings indicate that digital transformation significantly enhances the operational efficiency of SMEs in Vietnam. Furthermore, the study reveals that not only micro-level factors, such as firm age and fixed asset ratio, contribute to the efficiency of enterprises, but also macro-level factors, such as the economic growth rate of the province, play a role in enhancing the efficiency of SMEs. However, variables negatively affecting the operational efficiency of SMEs in Vietnam include firm size, financial accessibility, and the proportion of board members. Based on these findings, implications are discussed to assist SMEs in Vietnam in enhancing their efficiency in the digital economy.